The Role of Lighting Quality on the Risk of Visual Fatigue in Tahfidz Learning in Islamic Schools: A Literature Review - Diana Novitasari; Mahendra Wardhana (Syntax Corporation, 2026)
Classroom lighting plays a crucial role in supporting students' visual health. Inadequate lighting conditions may increase ocular accommodation load and trigger visual fatigue, particularly in Tahfidz learning activities that require sustained visual concentration over extended periods. Poor visual environments can negatively affect learning comfort, academic performance, and eye health. This study employs an integrative literature review approach by analyzing 20 open-access empirical and review articles related to classroom lighting quality and visual fatigue risk. The findings indicate that low illuminance, uneven light distribution, glare exposure, and suboptimal lighting quality are consistently associated with increased visual discomfort. In the context of Tahfidz learning, the risk is amplified due to intensive reading of Qur'anic text, which requires higher visual precision, recognition of small text, and prolonged near-vision tasks. The evidence suggests that classroom lighting is a key determinant of students' visual health. Lighting interventions, including glare control, window management, appropriate lighting selection, and regular illuminance evaluation, are essential to prevent visual fatigue in Tahfidz classrooms. This study highlights that lighting should be considered not only as a design factor but also as an environmental health concern.